(3TQM bUjOI GdHSJis - (3YHO Gddg GdeYQha HfbQg cGQs; (3CHh GdaJM Ydj Hf eMeO GdcGJH GdHSJj,J (B410 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd edM GdYdhe Yde GdYQHjI hHYO EdJeShG efi Cf CTQM GdbUjOI GdehSheI GdefShHI Edi CHj GdaJM GdHSJi s
(3BNQgG (B:s
(3gPG eCNhP ef bhd CejQ GdeDefjf Ydi QVi Gddg Yfg (B:" (3dG JfXQ Edi ef bGd hGfXQ Edi eG bGd EPG SeYJ cdGekG adG JfXQ Edi MGd bGFdg hdcf CfXQ Edi cKQI WGjdg (B" (3JeJ HYhf Gddg hMSf JhajbI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3hQO cTa GdXfhf L(B2 (3U (B1336 (3Cf bUjOI GdHSJi gi deDdagG CHh GdaJM Ydi Hf eMeO GdcGJH GdHSJJi GdeJhai SfI (B401 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3NRGfI Bd HGTf CYjGf GdHUQI (B(26 (3C(B) s
Keywords: (3GdeLGejYs